PENGEMBANGAN ALAT PERMAINAN EDUKATIF (APE) â€œKARTU BACA-NGAJI ASYIKâ€ SEBAGAI MEDIA BELAJAR BAGI ANAK USIA DINI DI TK AISYIYAH KECAMATAN SOKARAJA KABUPATEN BANYUMAS - Tutuk Ningsih (Jurnal Penelitian Agama, 2016)
Abstract: Playing methods are important in achieving the child's learning objectives. Therefore, educators should guide the course of the game in order not to hamper the development of children in terms of cognitive, affective, and psychomotor. Children are also given a place and opportunity as possible to play. Tools educational games (APE) are needed as a learning medium that will help the implementation of the method of play. In this study, at the design stage are at least three things to do, namely the analysis of concepts or ideas, translating the results of analysis of the concept, and describes the initial design of the game "Kartu Baca-Ngaji Asyik". Then the stage of development includes the setting up of pictures and text materials, preparing and designing the "Kartu Baca-Ngaji Asyik" game, print the results of the Ki "Kartu Baca-Ngaji Asyik" and create a game guidebooks. The results showed that the product" Kartu Baca-Ngaji Asyik" game generally good and fit for use as a medium of learning for young children. This is evidenced by the response, enthusiasm, and assessment scores from respondents and users. Players gave positive comments like fun, wants to return to play, and communicating with cheerful experience of playing on his friends. The concept and design of the game "Kartu Baca-Ngaji Asyik" simple makes it easy to develop and expanded materials by educators and parents. Keywords: Games Educational Tool, Media and Learning, Early Childhood